Modernity and Plato : Two Paradigms of Rationality - Adluri, Vishwa; Schmitt, Arbogast (Cambridge University Press, 2013)
Modernity's break with the Middle Ages is distinguished by a turn to a world of individual, empirical experience, a repudiation of Plato's idea of a reality of rationality and intellect. Yet already in the Renaissance it was no longer thought necessary to confront the ""old,"" Platonic concept of rationality. Arbogast Schmitt's book sets itself this until-now-unfulfilled task, howing that the Enlightenment did not, as often assumed, discover rationality, but instead a different 'concept' of rationality. It is a major contribution to synthetic philosophy and philosophical historiography, in Eng.